2004
DOI: 10.1177/1069072704266653
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy as a Mediator of the Relationships between Personality Factors and Career Interests

Abstract: Relationships among the Big Five personality factors (openness, conscientiousness, extraversion, agreeableness, and neuroticism), career interests, and career self-efficacy (using Holland’s realistic, investigative, artistic, social, enterprising, and conventional types for both of the latter) were examined. Among a sample of 147 college students, self-efficacy mediated four out of five personality-interest relationships that have been found to be robust across a number of other samples. The findings generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
3
15

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 26 publications
11
88
3
15
Order By: Relevance
“…In the first phase of the mediation effect analysis, Conscientiousness and Extraversion were associated with higher entrepreneurial self-efficacy, and these findings are consistent with previous studies [50,56] and these prior findings [51,53], respectively, as well as the cognitive-affective system theory of personality [37], which suggests the interaction between cognition and personality. Interestingly, Interpersonal Relationship was also positively related to entrepreneurial self-efficacy.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the first phase of the mediation effect analysis, Conscientiousness and Extraversion were associated with higher entrepreneurial self-efficacy, and these findings are consistent with previous studies [50,56] and these prior findings [51,53], respectively, as well as the cognitive-affective system theory of personality [37], which suggests the interaction between cognition and personality. Interestingly, Interpersonal Relationship was also positively related to entrepreneurial self-efficacy.…”
Section: Discussionsupporting
confidence: 80%
“…For example, Emotional Stability [11,54,56], Conscientiousness [11,50,56], Agreeableness [11,51,53], Extraversion [11,51,53], and Openness [11,52,56] were positively associated with self-efficacy respectively. These findings were based on a genetic perspective that personality traits are mostly inborn [11].…”
Section: Big Six Personality Related To Entrepreneurial Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The other related studies have shown minimal linkages between stress reaction or neuroticism and any of Holland's(1997) hexagonal interests (Barrick et al, 2003;Staggs et al, 2007) or self-efficacy themes (Larson & Borgen, 2006;Nauta, 2004). As expected, alienation was not shown to vary across major families based on prior studies (Larson & Borgen, 2006;Staggs et al, 2007).…”
Section: Personality Alonementioning
confidence: 56%
“…Ainsi, sort-on de l'écueil personnologique consistant à réduire la compréhension des transactions individu/ environnement à des caractéristiques générales et stables de personnalité: pour Betz et Hackett (2006), les SEP ne sont pas des «concepts-traits». Ceci ne signifie pas une absence d'effet des traits de personnalité, mais une prise en compte de la médiation de cet effet par des dimensions plus sensibles au contexte (Brown et al, 2006;Lent & Brown, 2006b;Nauta, 2004). Cette spécificité oblige à adapter les variables ou à en créer de nouvelles, dès lors que l'on s'intéresse à un domaine non encore étudié (Betz & Hackett, 2006).…”
unclassified